Integrated Marketing in the Digital Age: Maximizing Communication Tools for Management Success - Diyal, Suresh Bahadur (Educational Journal, 2024)
This study investigates the management of marketing communication in the digital era, emphasizing the transformative role of Information and Communication Technology (ICT). Rapid technological advancements and shifting consumer behaviors have expanded communication channels, creating opportunities and challenges for businesses to maintain consistent and effective brand messaging. Using a qualitative research approach, data were collected from secondary sources, including scholarly articles, books, and industry reports, and analyzed inductively to explore current practices and trends. The findings highlight that effective management of marketing communication requires strategic alignment of messages, integration of digital platforms, and utilization of tools such as social media, open innovation, and targeted marketing to enhance engagement and brand loyalty. Results also show that businesses leveraging ICT-driven strategies—such as influencer collaboration, real-time customer interaction, and word-of-mouth amplification—achieve higher communication efficiency and stronger customer relationships. This study contributes by providing a comprehensive synthesis of management strategies for marketing communication in the digital age and offers actionable insights for practitioners, scholars, and educators.